Synchrotron-Radiation X-Ray Investigation of Li+/Na+ Intercalation into Prussian Blue Analogues - Yutaka Moritomo; Masamitsu Takachi; Yutaro Kurihara; Tomoyuki Matsuda (Advances in Materials Science and Engineering)
Prussian blue analogies (PBAs) are promising cathode materials for lithium ion (LIB) and sodium ion (SIB) secondary batteries, reflecting their covalent and nanoporous host structure. With use of synchrotron-radiation (SR) X-ray source, we investigated the structural and electronic responses of the host framework of PBAs against Li+ and Na+ intercalation by means of the X-ray powder diffraction (XRD) and X-ray absorption spectroscopy (XAS). The structural investigation reveals a robust nature of the host framework against Li+ and Na+ intercalation, which is advantageous for the stability and lifetime of the batteries. The spectroscopic investigation identifies the redox processes in respective plateaus in the discharge curves. We further compare these characteristics with those of the conventional cathode materials, such as, LiCoO2, LiFePO4, and LiMn2O4.